2002
DOI: 10.1186/1472-6750-2-17
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between two brine shrimp assays to detect in vitrocytotoxicity in marine natural products

Abstract: Background: The brine shrimp lethality assay is considered a useful tool for preliminary assessment of toxicity. It has also been suggested for screening pharmacological activities in plant extracts. However, we think that it is necessary to evaluate the suitability of the brine shrimp methods before they are used as a general bio-assay to test natural marine products for pharmacological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(105 citation statements)
references
References 20 publications
(24 reference statements)
4
92
0
9
Order By: Relevance
“…It indicates that the lethality effect of leaf extract is time dependent, increasing significantly after 24 h exposure. At this time nauplii are mainly in instar II/III [4] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It indicates that the lethality effect of leaf extract is time dependent, increasing significantly after 24 h exposure. At this time nauplii are mainly in instar II/III [4] .…”
Section: Discussionmentioning
confidence: 89%
“…It is used as a "benchtop bioassay" for the discovery and purification of bioactive natural products and is an excellent choice for elementary toxicity investigations of consumer products. The shrimp lethality assay is based on the ability to kill laboratory-cultured Artemia nauplii (animal's eggs) [4] . …”
Section: Introductionmentioning
confidence: 99%
“…Each treatment and control sample was distributed in triplicate into the sterile petri-dish before incubation at 28 °C under constant illumination in a digital incubator (MRC Laboratory Equipment, Model LE-509). Thereafter, the petri-dishes were examined with the aid of a hand lens against a white background that allows the moving larvae (naupili) to be separated from shells and counted at every 12 h for 72 h. The percentage hatchability was calculated by comparing the number of hatched naupili with the total number of brine shrimp eggs stocked (Carballo et al, 2002).…”
Section: Hatchability Test Of Brine Shrimpsmentioning
confidence: 99%
“…35 Results are given in Table 2 for the compounds which exhibited optimal cytotoxic effect against cancer cell lines, being the eight compounds 2b, 6, 11b, 11c, 12b, 16a, 16b and 18a. The shrimp lethality assay is considered as a useful tool for preliminary assessment of toxicity, and it has been used for the detection of fungal toxins, plant extract toxicity, heavy metals, cyano bacteria toxins, pesticides, and cytotoxicity testing of dental materials, 36 natural and synthetic organic compounds. 34 It has also been shown that A. salina toxicity test results have a correlation with rodent and human acute oral toxicity data.…”
Section: Toxicitymentioning
confidence: 99%